Paul Tillich's Concept of "Ultimate Concern" for Sustainable Inter-Religious Dialogue - Suot, Emil John; Sudhiarsa, Raymundus I Made; Tinambunan, Edison Robertus Lamarsen; Kristianto, Stefanus (International Journal of Indonesian Philosophy & Theology, 2025)
Indonesia’s rich diversity in ethnicity, culture, religion, and beliefs is a national strength and a potential source of conflict. Instances such as public opposition to the construction of places of worship in various regions demonstrate how religious differences can fuel conflicts. In this context, inter-religious dialogue is vital in preventing and resolving conflicts within religiously plural communities. The harmonious relationship between Muslims and Christians in Sambikerep Village, Surabaya, motivated the author to investigate this subject. This article explores Paul Tillich’s concept of “Ultimate Concern” as a framework for understanding the experiences of research participants in Muslim-Christian dialogue. This phenomenological study aims to highlight the importance of Tillich's concept in promoting sustainable inter-religious dialogue and fostering long-term peace and understanding. For this study, the author employed Heidegger’s hermeneutic phenomenological method, utilized in-depth interviews to collect data, and conducted observations to confirm the authenticity of the interview findings. The three main findings of this article are: the importance of viewing religion as a concept that helps balance the opposing aspects of religious content and practice; inclusivism as a path for interreligious dialogue that does not dilute personal convictions; and the courage to participate in a humanist community, which fosters sustainable interreligious dialogue by overcoming the fear of rejection.